2017
DOI: 10.1007/s12080-017-0349-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic choices are most accurate in small groups

Abstract: According to the classic results of Galton and Condorcet, as well as in modern decision-making models, accuracy in groups increases with group size. However, these studies do not consider the naturally occurring situation in which individuals dynamically re-evaluate their decision with a possible change of opinion. The dynamics of re-evaluation in groups are very different to individual re-evaluation because individuals influence the group and the group influences the individual. We find that individual accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…In natural environments, animals typically do not make judgments completely independently of each other, as assumed in our analysis so far, and in models such as the Condorcet jury theorem. Instead, the opinions of animals are often correlated with each other to some degree, and in such scenarios, small group sizes have often been shown to maximize collective accuracy [16,18]. This is because increasing group size initially increases collective accuracy owing to the benefit of opinion aggregation (the ‘wisdom of crowds’), but at larger group sizes, the correlated cue increasingly dominates the collective decision, decreasing accuracy.…”
Section: Modular Structure Can Improve Accuracy In Complex Environmentsmentioning
confidence: 99%
“…In natural environments, animals typically do not make judgments completely independently of each other, as assumed in our analysis so far, and in models such as the Condorcet jury theorem. Instead, the opinions of animals are often correlated with each other to some degree, and in such scenarios, small group sizes have often been shown to maximize collective accuracy [16,18]. This is because increasing group size initially increases collective accuracy owing to the benefit of opinion aggregation (the ‘wisdom of crowds’), but at larger group sizes, the correlated cue increasingly dominates the collective decision, decreasing accuracy.…”
Section: Modular Structure Can Improve Accuracy In Complex Environmentsmentioning
confidence: 99%
“…Alignment on utility functions may be more difficult to achieve in diverse groups, but then, perhaps if an ultimate consensus utility is achieved it could be better for more people outside the group. Group size has also been a topic of interest (Kao & Couzin, ; Vicente‐Page, P′erez‐Escudero, & Polavieja, ). It is plausible that alignment is easier to achieve in small groups due purely to statistical effects of distributions of beliefs and preferences.…”
Section: Relationship With Existing Theoriesmentioning
confidence: 99%
“…As a mechanism, it has been found that probabilistic response scales enrich social learning by allowing individuals to explicitly signal uncertainty in their judgments [20][21][22][23][24][25][26][27]. By contrast, exchanging coarse-grained binary judgments can prevent individuals from signaling their uncertainty-for example, when voting 'yes' or 'no' on whether an event will occur, different people may vote 'no' with either high or low confidence; the binary signal alone does not distinguish among them [28][29][30]. Moreover, probabilistic response scales allow individuals to signal even minor belief adjustments during the communication process that can help steer the group toward a more accurate collective judgment [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%